ระบบแคชแบบปรับเปลี่ยนรหัสข้อมูลสำหรับอุปกรณ์โทรศัพท์เคลื่อนที่อัจฉริยะ - ปิติพงศ์ พงศ์ภัทรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
We present Transcoding Cache (TC), a new way for caching data in smart phone application using web service. Transcoding Cache adapts the cache data for better utilization of limited space. Without changing the cache algorithm, TC works by transcoding the cache data in the disk cache. Our experiments show that TC performs better than the normal cache system. In particular, we can reduce the data transmitted through the mobile network up to 15% comparing to the legacy cache system.